Stability is the “core principle” in the development of guided bone regeneration of alveolar bone - WU Jing; ZOU Duohong (Kouqiang hemian waike zazhi)
Guided bone regeneration (GBR) has been proved to be an efficient technique for alveolar bone augment in more than 40 years' clinical practice. The fundamental components of GBR technology involve ensuring ample blood supply and establishing a stable environment. However, current GBR technology primarily operate under the theoretical framework of "blood supply-core principle" with insufficient emphasis on the significance of stability. Through thorough literature review and a series of clinical trials, we propose a paradigm shift — a dental alveolar bone repair and reconstruction concept centered on "stability-core principle". Under this innovative approach, we have introduced a novel treatment method that utilizes exclusively artificial bone powder for the repair of severe dental alveolar bone defects. This groundbreaking development challenges the conventional international practice that necessitates the use of autogenous bone for bone defect repairs. This article delves into the historical trajectory of GBR technology, highlighting the critical importance of stability. Integrating this insight with existing bone regeneration theories, we provide a detailed exposition on the new technique for dental alveolar bone repair and reconstruction, centered around the core principle of "stability".